Associations Between Openness Facets, Prejudice, and Tolerance: A Scoping Review With Meta-Analysis - Ng, D. X.; Lin, Patrick K. F.; Marsh, Nigel V.; Chan, K. Q.; Ramsay, Jonathan E. (Frontiers in Psychology, 2021)
The personality factor of openness to experience, which encompasses curiosity, imagination, and a desire for new experiences, has been associated negatively with prejudice and positively with the closely related value of tolerance. While these relationships have been reviewed at the factor level, there has been no review of research at the lower facet level. This review aims to uncover the relationships between the facets of openness and the constructs of prejudice and tolerance. We conducted a pre-registered scoping review with meta-analysis following the Joanna Briggs Institute recommended guidelines. A total of 2349 articles were reviewed, with 16 primary research articles (or 17 studies) meeting the criteria for inclusion. Aggregated effect sizes via random-effect meta-analysis revealed that all NEO-PI-R and IPIP-based facets of openness significantly predicted prejudice and tolerance. Out of the three measures (i.e., NEO-PI-R, IPIP-NEO, and HEXACO-PI) and facets of openness examined, the NEO-PI-R facet of value was most strongly associated with prejudice. In contrast, the NEO-PI-R facet of aesthetics was the facet most strongly associated with tolerance. However, these results should be treated as preliminary in light of the small number of meta-analysed studies and more primary research are needed to confirm the trends found in this review. This review represents the first step in the systematic investigation of the link between facets of openness and components of prejudice and tolerance and contributes towards explaining prejudice and tolerance.